2011
DOI: 10.1165/rcmb.2010-0315oc
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Dependent Genomic Factors Affect Allergen-Induced Airway Hyperresponsiveness in Mice

Abstract: Asthma is etiologically and clinically heterogeneous, making the genomic basis of asthma difficult to identify. We exploited the straindependence of a murine model of allergic airway disease to identify different genomic responses in the lung. BALB/cJ and C57BL/6J mice were sensitized with the immunodominant allergen from the Dermatophagoides pteronyssinus species of house dust mite (Der p 1), without exogenous adjuvant, and the mice then underwent a single challenge with Der p 1. Allergic inflammation, serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 45 publications
6
52
0
2
Order By: Relevance
“…A mutation in Cftr led to airway hyperresponsiveness in the BALB Cftr tm1UNC mice, but not in B6 Cftr tm1UNC mice; this finding is consistent with the strain-dependent lung function in challenge models (35,36,45,46) and likely occurred through an increase in pulmonary CD3 + cells. The absence of altered lung function in B6 Cftr tm1UNC mice agrees with previous airway response phenotyping of this strain (47), although changes in breathing rate and minute volume (48,49) have been reported for B6 Cftr tm1UNC mice; therefore, lung function changes apart from airway hyperresponsiveness may exist in this strain.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A mutation in Cftr led to airway hyperresponsiveness in the BALB Cftr tm1UNC mice, but not in B6 Cftr tm1UNC mice; this finding is consistent with the strain-dependent lung function in challenge models (35,36,45,46) and likely occurred through an increase in pulmonary CD3 + cells. The absence of altered lung function in B6 Cftr tm1UNC mice agrees with previous airway response phenotyping of this strain (47), although changes in breathing rate and minute volume (48,49) have been reported for B6 Cftr tm1UNC mice; therefore, lung function changes apart from airway hyperresponsiveness may exist in this strain.…”
Section: Discussionsupporting
confidence: 77%
“…We are not aware of prior reports of the lung function in BALB Cftr tm1UNC mice. Regarding mechanism, strain-dependent increases in mucus (36) or in smooth muscle (46) have been implicated in the development of the hyperresponsive trait in BALB mice, but they do not appear to contribute to the differences identified in this study. Indeed, that we did not detect an increase in the number of PAS positive cells in the lungs of BALB Cftr tm1UNC mice, even in the presence of an enhanced Th2 environment, is consistent with the findings of Hauber et al (50), who showed that explanted mucosal tissue from CF patients did not produce increased amounts of MUC5AC or mucin protein following IL-4 or IL-13 stimulation in vitro.…”
Section: Discussionmentioning
confidence: 58%
“…On day 14, mice were challenged with 50 mg of Der p 1, administered by orotracheal aspiration (Kelada et al 2011;Kelada et al 2014). Mice were phenotyped on day 17 by performing lavage followed by differential cell counts.…”
Section: Phenotyping Protocolmentioning
confidence: 99%
“…There is ample prior evidence that these traits have a genetic basis (Levitt and Mitzner 1988;Brewer et al 1999;Whitehead et al 2003;Kelada et al 2011) and QTL have been identified for airway hyperresponsiveness on several chromosomes (De Sanctis et al 1995Karp et al 2000;Ackerman et al 2005;Camateros et al 2010;Leme et al 2010;Himes et al 2013). However, a systematic evaluation of whether variation in gene expression underlies these traits has not been conducted.…”
mentioning
confidence: 99%
“…Pode ser seguido ou não da presença de adjuvante 10 . Reproduz muitas características da asma, como elevado nível de inflamação das vias aéreas, IgE 20 Significativo aumento de linfócitos, macrófagos e da produção de muco.…”
Section: Discussionunclassified